Aquaculture systems and pathological problems of new species reared in fresh water in Greece - RAGIAS (Β. ΡΑΓΙΑΣ), B.; ATHANASSOPOULOU (Φ. ΑΘΑΝΑΣΟΠΟΥΛΟΥ), F. (Journal of the Hellenic Veterinary Medical Society, 2017)
Published data on growth and pathology of the fish species: Mugil cephalus (mullet) and Acipenser gueldestaedi (sturgeon), under intensive culture, is limited. In particular, data on dietary requirements is non-existing. For the artificial feeding of these fish, other feeds originally prepared for other cultured fish species are used (trout and/or sea bass, sea bream pelleted feeds). Mugil cephalus is very tolerant to intensive rearing and the main problem observed was recurrent infections by Chilodonella sp. Mugilids reared in lagoons are infected with a variety of parasites, but these do not cause problems and mortality. Acipenser gueldestaedi is a very desirable fish for rearing, because of the fast growth rate, the good digestibility of food, even with no specific diets and the ability to be cultured under different systems. Furthermore, it has a wide temperature tolerance, it is very tolerant to stress and the mortality at fish> 5cm is less than 5%. Disease experiences from rearing sturgeon are reported mainly from N. America and concern viral infections. In Greece, Acipenser gueldestaedi seems to be very susceptible to both Noda virus and spinal deformities after the weight of 500g. Fish in open flow systems started to show skeletal abnormalities with increasing prevalence. Histopathology investigations, both in Greece and Canada, were inconclusive as to the aetiology of these skeletal deformities. These could not be proved to be associated with the feed of the fish. These deformities have been observed before in cultured sturgeon, but they are not yet fully investigated. At a later stage, fish cannot swim properly, do not feed and soon succumb to secondary infections by Aeromonas hydrophila.